2016
DOI: 10.1017/s1049023x16000704
|View full text |Cite
|
Sign up to set email alerts
|

Are Pediatric Emergency Physicians More Knowledgeable and Confident to Respond to a Pediatric Disaster after an Experiential Learning Experience?

Abstract: Advanced learners exposed to an experiential learning activity believed that it improved their ability to manage patients in a disaster situation and felt that it was valuable to their learning. Their confidence was preserved six months later. Bank I , Khalil E . Are pediatric emergency physicians more knowledgeable and confident to respond to a pediatric disaster after an experiential learning experience? Prehosp Disaster Med. 2016;31(5):551-556.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…These benefits align with evaluations of in-person tabletop exercises, 11,12 including exercises targeting children's needs. 31,32 However, barriers including resource constraints, staff turnover, and inconsistent planning priorities were noted, consistent with previous studies. 8 Our findings expand upon limitations of extant research [10][11][12] by identifying the degree to which improvements persist and translate to concrete local preparedness actions 6 months later.…”
Section: Lessons Learnedsupporting
confidence: 84%
“…These benefits align with evaluations of in-person tabletop exercises, 11,12 including exercises targeting children's needs. 31,32 However, barriers including resource constraints, staff turnover, and inconsistent planning priorities were noted, consistent with previous studies. 8 Our findings expand upon limitations of extant research [10][11][12] by identifying the degree to which improvements persist and translate to concrete local preparedness actions 6 months later.…”
Section: Lessons Learnedsupporting
confidence: 84%
“…Importantly, we found that only a few physicians in each centre were trained in trauma, despite that most of them would be required in case of a disaster. In addition, teaching sessions focused on triage and identification of victims, and we observed a lack of training regarding specific disorders encountered in disasters 13. To improve paediatric disaster readiness and implication of healthcare professionals, paediatric victims should be included in simulation scenarios, teaching objectives should be refined and methods broadened along with harmonisation across centres.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unpredictable nature of MCIs, day-to-day protocols are insufficient to effectively manage the evolution of an MCI, specifically, the inability to manage severe resource constraints [8,[11][12][13]. Normal hospital procedures do not prepare staff for patient surges that may exceed the available resources [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%